Further Data About the Distribution of the Moss Bryum gemmiferum (Bryophyta, Bryaceae) in Poland - Grzegorz Vončina; Adam Stebel; Anna Rusińska; Mirosław Szczepański; Stanisław Rosadziński; Michał Smoczyk; Paweł Kalinowski (Acta Societatis Botanicorum Poloniae, 2022)
This paper presents the information on the distribution of the moss Bryum gemmiferum R. Wilczek Demaret in Poland. The first species site from southern Poland was published, but further research and revision of the herbarium materials provided information about its occurrence in different parts of the country. Currently, this species is known in 20 locations. A brief discussion about its ecology, taxonomy, and geographical distribution is given.